2022
DOI: 10.3389/fpls.2022.824948
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Ethylene and Abscisic Acid During Changes in Soil Water Content Reveals a New Role for 1-Aminocyclopropane-1- Carboxylate in Coffee Anthesis Regulation

Abstract: Coffee (Coffea arabica L.) presents an asynchronous flowering regulated by an endogenous and environmental stimulus, and anthesis occurs once plants are rehydrated after a period of water deficit. We evaluated the evolution of Abscisic Acid (ABA), ethylene, 1-aminocyclopropane-1-carboxylate (ACC) content, ACC oxidase (ACO) activity, and expression analysis of the Lysine Histidine Transporter 1 (LHT1) transporter, in the roots, leaves, and flower buds from three coffee genotypes (C. arabica L. cv Oeiras, Acauã,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 89 publications
(108 reference statements)
1
6
0
Order By: Relevance
“…Connected to this model of transcriptional regulation of ethylene biosynthesis genes, it has been demonstrated that ethylene levels in coffee roots are reduced during the dry season and increased after rehydration, preceding anthesis (López et al, 2022). In this study, the ethylene level was measured in leaves and floral buds of the coffee genotypes Oeiras, Acauã and Sf (Fig.…”
Section: Hormonal Regulation In Coffee Floweringmentioning
confidence: 73%
See 2 more Smart Citations
“…Connected to this model of transcriptional regulation of ethylene biosynthesis genes, it has been demonstrated that ethylene levels in coffee roots are reduced during the dry season and increased after rehydration, preceding anthesis (López et al, 2022). In this study, the ethylene level was measured in leaves and floral buds of the coffee genotypes Oeiras, Acauã and Sf (Fig.…”
Section: Hormonal Regulation In Coffee Floweringmentioning
confidence: 73%
“…Ethylene quantifications were made using leaves and floral bud tissues collected at different time points (see Fig. S1 for details), following the method described in López et al (2022), with the production rate expressed as ppm. g -1 FW.…”
Section: Carbohydrates and Ethylene Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-Time Quantitative PCR (RT-qPCR) was performed with the Rotor-Gene SYBR® Green PCR Kit (Qiagen), on a Rotor Gene-Q(R) thermocycler (Venlo, Netherlands) using three biological repetitions runned in three technical replicates as described by López et al, (2022). The expression rate and the confidence intervals were calculated according to the method proposed by Steibel et al, (2009), which considers the linear mixed-effect model.…”
Section: Rna Extraction and Real-time Quantitative Pcr (Rt-qpcr) Anal...mentioning
confidence: 99%
“…Orthologs of FT have been identified in several species such as rice (Tamaki et al, 2007), coffee (Cardon et al, 2022) and many others (Pin and Nilsson, 2012). FT belongs to the PHOSPHATIDYLETHANOLAMINE-BINDING PROTEIN (PEBP) family, which is conserved in plants and animals (Jin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%